Analysis of Role, Challenges, and Impact of Educational Supervision on Teacher Professional Development - Ruchmayano, Nova Virdamahaputra; Suryadi, Suryadi; Nurdin, Diding; Khofifah, Juliani Musti (Newinera Publisher, 2025)
The tension between institutional accountability and pedagogical autonomy remains a central challenge in school leadership, yet the mechanisms modulating this interplay within professional development are often overlooked. This study examines the operational synergy between supervisory roles, systemic challenges, and teacher growth through a quantitative analysis of 27 practitioners. Findings reveal a high-performance baseline in supervisory roles (Mean 4.21), anchored by rigorous curriculum alignment (Mean 4.48) and consistent clinical observations (Mean 4.26). We identify a critical